Emerald - Australia. Division of National Mapping ([Canberra] : NATMAP, 1981)
Topographic map with relief shown by contours, spot heights, form lines and hill shading.
Index to adjoining sheets.
Keywords: Emerald (Qld.) -- Maps; Topographic maps